EFEKTIVITAS PENGGUNAAN PROYEKTOR DALAM PENGAJARAN BAHASA INGGRIS PADA PENDIDIKAN ANAK USIA DINI - Gumilar, Yogi; Budi Utami, Fitria; Lestari, Maya; Ulfah Mawaddah, Fahmy (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2024)
This study investigates the effectiveness of using projectors for teaching English in early childhood education, focusing on teachers' perceptions, the impact on student attention and understanding, and the challenges encountered. Technological advancements, particularly the use of projectors, have been shown to enhance educational experiences by making lessons more engaging and interactive. This research employed a qualitative descriptive method, interviewing 12 kindergarten teachers in Tangerang to gather insights on their experiences with projectors. Findings indicate that teachers generally view projectors positively, appreciating their ability to capture students' attention and facilitate comprehension of basic English concepts. Projectors are effective in providing clear visual content and supporting multisensory learning, but their impact is influenced by factors such as the teacher's proficiency, content relevance, and classroom environment. Challenges include limited availability of projectors, inadequate technical training, and difficulties in maintaining young children's attention. The study underscores the need for improved access to technology, better teacher training, and thoughtful integration of projectors into teaching practices. Future research should explore the long-term effects of projector use and develop best practices for their implementation in early childhood education.